CircularEconomy4Colombia: Bootcamp Report: Innovation Challenge 2024 - Menza, Gianpiero; Khader, Taija (2025)
In the context of CGIAR Research Initiative Nature-Positive Solutions, the CircularEconomy4Colombia Innovation Challenge is powered by the CGIAR Accelerate for Impact Platform (A4IP) and co-organized with CGIAR Centers – the Alliance Bioversity International-CIAT and the International Water Management Institute (IWMI) – in partnership with EAN University, Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ), and the Green Business Office of Colombia's Ministry of Environment and Sustainable Development (Minambiente).